Comparative analysis of several methods for blood pressure measurement in the morning in patients with arterial hypertension - G. F. Andreeva; A. D. Deev; V. M. Gorbunov (Кардиоваскулярная терапия и профилактика, 2018)
Aim. To compare the known methods of blood pressure (BP) measurement in the morning and a new method for estimating the average morning BP for fixed time intervals, comparing their reproducibility and validity.Material and methods. We analyzed database containing 983 cases of ambulatory blood pressure monitoring (ABPM). Results of ABMP in patients with hypertension without severe associated diseases and weekly cancellation of antihypertensive therapy were analyzed. Blood pressure data per 24-hour period, day and night, level and rate of morning BP surge were assessed. In addition, we proposed new method for estimating the average morning BP level for fixed time intervals, based on calculating the average BP level for the following time windows: from 5:00 to 7:00 a.m., from 7:00 to 9:00 a.m., from 9:00 to 11:00 a.m. To assess the reproducibility of the new method, we determined correlations between the first and second group results calculated by the new method based on two repeated ABPM conducted with 1-2 weeks interval (n=90). To study the validity of the new method for measurement of average morning BP level, we used an objective validation criterion — Left Ventricular Myocardium Mass Index (LVMMI). There were performed 98 echocardiographic tests with the use of Acuson 128XP. LVMMI was calculated using the L. Teichholtz method (1976).Results. The new method for measurement of average morning BP level had good reproducibility while the reproducibility of dynamic showings of ABMP (level and rate of morning BP surge) was low. A new method for assessing morning blood pressure was characterized by a high level of validity: the indicators obtained using this technique reliably correlated with the validation criteria: LVMI and the average daily blood pressure level.Conclusion. The proposed new method for estimating the average morning level of blood pressure has a high level of validity and reproducibility. Time interval from 7 to 9 a. m. seems to be the most optimal. The maximum reproducibility of the showings was noted during this period.